Preparation and characterization of UV‑cured epoxy acrylate‑based nanocomposite coatings containing organonanoclay - KARATAŞ, SEVİM; MADAKBAŞ, SEYFULLAH (My University, 2022)
In this study, it is aimed to obtain UV-cured nanocomposite coatings. UV-curable epoxy acrylate resins were synthesized by reacting aliphatic-based epoxy resin with adipic acid and acrylic acid at certain rates and their chemical structures were characterized. The synthesized resins were reinforced with organonanoclay at diferent rates, applied as a flm to plexiglass surfaces and cured with UV rays. The thermal properties, fammability, thermomechanical properties, surface properties, morphological properties, light transmittance and durability properties of the obtained nanocomposite coatings containing organonanoclay were investigated. With 5% organonanoclyay reinforcement to the epoxy acrylate resin, the temperature of fnal mass loss increased from 521 to 557 °C, char yield increased from 0.02% to 2.95, LOI increased from 22.1 to 23.5%, contact angle increased from 56 to 74°. The results showed that UV-cured nanocomposite coatings have the properties required by the coating industry, and these properties are improved with the addition of organonanoclay. Keywords Nanocomposite · Coating · UV-cured · Epoxy acrylate · Organonanoclay
Keywords: Kimya; Temel Bilimler; Chemistry; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; CHEMISTRY; MULTIDISCIPLINARY SCIENCES; Kimya (çeşitli); Genel Kimya; Multidisipliner; Fizik Bilimleri; Chemistry (miscellaneous); General Chemistry; Multidisciplinary; Physical Sciences; Nanocomposite; Coating; UV-cured; Epoxy acrylate; Organonanoclay